Hubungan Obesitas dengan Kadar Kolesterol Total pada Penderita Obesitas di Wilayah Pesisir Kapoiala - Sudayasa, I Putu; Afrini, Ida Mardhiah; Azzahra, Inayah (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
Obesity is a major risk factor associated with metabolic disorders, including dyslipidemia, which can increase total cholesterol levels. This study aims to analyze the relationship between obesity and total cholesterol levels in obese individuals in the coastal area of Kapoiala. This study used an observational design with a cross-sectional approach. The respondents consisted of individuals with obesity, divided into two groups: obesity 1 and obesity 2. Demographic data, obesity levels, and total cholesterol levels were measured and then analyzed using Odds Ratio (OR) to assess the relationship between obesity and cholesterol levels. The majority of respondents were in the age range of 30–49 years, with a high school education as their last level of education, and most worked as housewives. In the obesity 1 group, 71.4% had high cholesterol levels, while in obesity 2, the distribution of normal and high cholesterol levels was relatively balanced. The obtained Odds Ratio was 0.873 (95% CI: 0.314–2.428), indicating no significant relationship between the level of obesity and total cholesterol levels. This study shows that although obesity is a risk factor for increased cholesterol levels, this relationship is not statistically significant. Other factors, such as diet and genetics, may also influence cholesterol levels.